2015
DOI: 10.1007/s11764-015-0460-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second primary cancers in North Portugal—a population-based study

Abstract: SPC constitute an important dimension of the burden of cancer survivorship, and this needs to be taken into account when defining strategies for surveillance, prevention and counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…gastric cancer patients were also the colon and rectum [10]; however, it did not show a significant risk of SPCs diagnosed more than two or 12 months after the gastric FPC [36]. In the present study, because of the larger sample size and longer follow-up period, we observed a significant increased risk of SPC after two months in males and though our estimate for SPCs defined using a 12 month gap was not statistically significant, it was more precise.…”
Section: Discussioncontrasting
confidence: 69%
“…gastric cancer patients were also the colon and rectum [10]; however, it did not show a significant risk of SPCs diagnosed more than two or 12 months after the gastric FPC [36]. In the present study, because of the larger sample size and longer follow-up period, we observed a significant increased risk of SPC after two months in males and though our estimate for SPCs defined using a 12 month gap was not statistically significant, it was more precise.…”
Section: Discussioncontrasting
confidence: 69%
“…7 Several studies in high-income countries have reported that cancer survivors are at higher risk of subsequent diagnosis with another cancer relative to the general population. [2][3][4][8][9][10][11] While the extent of such associations varies depending on the types of the first and second cancers, strong associations are seen between lifestyle-related (e.g. smoking and alcohol consumption) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Developing multiple primary cancers has become a common rather than rare event that patients and clinicians encounter. 1 , 2 , 3 , 4 Of all cancer survivors, the incidence of multiple primaries is reported to be in the range of 2%–17%. 1 , 2 , 3 , 4 , 5 In our previous assessments in Osaka, Japan, 2.0% of cancer survivors developed a second primary cancer within 10 years of first diagnosis during 1966–1989, 6 and this proportion rose nearly double (3.8%) by 1985–2005.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Tabuchi et al [4] reported that the incidence of metachronous malignancies has almost doubled over the last two decades. Pacheco-Figueiredo et al [5] concluded that the incidence of malignancies is higher in cancer survivors than the general population. The International agencies for research on cancer define multiple primary cancers as those cancers that originally developed in an organ or tissue and are not an extension, recurrence or metastasis.…”
Section: Discussionmentioning
confidence: 99%